Romania : Report on Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2001)
This Report on Observance of Standards and Codes analyzes the principal standard against which Romania's macroeconomic and sociodemographic data are assessed. With some exceptions, the statistics currently produced in Romania generally meet, and in most instances exceed, the recommendations of the General Data Dissemination System with respect to coverage, periodicity, and timeliness of dissemination. However, with respect to other aspects of quality, further improvements are needed, especially in national accounts and government finance statistics and, to a lesser extent, in other sectoral statistics.